Unlocking customer engagement via Gamification dynamics in Sri Lankan E-tailing - Rajumesh, S.; Karunanithy, M.; Kajenthiran, K. (University of Jaffna, 2023)
Gamification, widely adopted in various industries, is recognized as a valuable strategy for enhancing customer engagement. In the Sri Lankan e-tailing context, where online shopping has become integral, gamification can significantly impact customer participation and their behavioral outcomes like satisfaction, loyalty, etc. The study aimed to investigate the influence of gamification on customer engagement within the Sri Lankan e-tailing context, utilizing the Self-Determination Theory as a theoretical framework. Furthermore, the present study explores the moderating roles of perceived usefulness and perceived ease of use in the association between gamification and customer engagement. A comprehensive survey was conducted with 541 participants, and partial least squares (PLS) in the SmartPLS4 were employed to test the formulated hypotheses empirically. The study's findings indicate that gamification, perceived usefulness and perceived ease of use significantly strengthen customer engagement. Moreover, perceived ease of use was observed to enhance the relationship between gamification and customer engagement. This study’s conclusions hold significance for theoretical and managerial perspectives. These findings can be valuable for academics in refining theoretical frameworks and for managers seeking practical guidance in optimizing gamification approaches for enhanced customer engagement in relevant contexts.
Keywords: Gamification; Customer engagement; E-tailor; Perceived usefulness; Perceived ease of use